An Automated flight control system for quad-rotor flying vehicle using embedded microcontroller - Chan, Ai Ling. (2011)
Research interest into vertical take-off and landing(VTOL) aircraft has been prominent in recent years due to the rapid development of technology in the area and the numerous advantages VTOL aircraft have over traditional airplanes and helicopters.